Isolation and Selection of Sulfuric Acid Bacteria from Kejayan River as Bio-oxidation Agents - Ulya, Fahimatul (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
Biooxidation method is connsidered more environmentally friendly and more economical to be able to overcome environmental problems polluted by metals. Sulfuric acid-producing bacteria is one of the biooxidizing agents, these bacteria can be isolated from acidic soil or acidic areas. The Kejayan Pasuruan River is drained by various industrial acidic wastes that contain metals. This study aims to obtain sulfuric acid-producing bacteria from the Kejayan river. Isolation and selection of sulfuric acid-producing bacteria from Kejayan river soil using thiosulfate medium. Pure isolates were obtained using the streak plate quadrant. In the biooxidation process using CuFeS2, sulfuric acid levels were measured using the turbidimetric method, the levels of [Cu] and [Fe] in the biooxidation medium were tested using AAS (Atomic Absorption Spectroscopy). K.2 isolate was selected as sulfuric acid producing bacteria with the highest sulfate concentration [SO42-] 13.9 ppm at 48 hours. These bacteria have the potential as biooxidizing agents for Cu and Fe metals.